The price of freedom: criminalization and the management of outsiders in Germany and the United States - Soyer, Michaela (University of California Press, 2024)
"Seeking to shed light on how we might end mass incarceration, The Price of Freedom compares the histories and goals of the American and German justice systems. Drawing on repeated in-depth interviews with incarcerated young men in the United States and Germany, Michaela Soyer argues that the apparent relative lenience of the German criminal justice system is actually founded on the violent enforcement of cultural homogeneity at the hands of the German welfare state. Demonstrating how both societies have constructed a racialized underclass of outsiders over time, this book emphasizes that criminal justice reformers in the United States need to move beyond European models in order to build a truly just, diverse society"--